Methods for breaking Chinese lantern (Physalis alkekengi L.) seed dormancy. Laboratory and greenhouse studies - Asgari, Ashkan; Rezvani Moghaddam, Parviz; Koocheki, Alireza (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2018)
In order to evaluate different methods of seed dormancy breaking for Chinese lantern (Physalis alkekengi L.), two experiments were conducted at laboratory and greenhouse conditions. The laboratory treatments were 22 different physical and chemical methods such as washing, stratification, scarification (sandy paper), sulfuric acid, gibberellic acid, potassium nitrate and the combination of both physical and chemical treatments. Eight of the best breaking seed dormancy treatments at the laboratory study were assessed at the greenhouse study. The results of the first experiment showed that all the treatments had significant effects on the measured traits. The highest germination percentage was shown in the combinational treatments (washing + gibberellic acid, sulfuric acid + potassium nitrate, scarification + gibberellic acid and scarification + potassium nitrate). These treatments led to 100% germination. The minimum mean germination time (MGT) was found in the washing + gibberellic acid (3.89 days), washing + potassium nitrate (4.42 days) and stratification + gibberellic acid (4.79 days) treatments. Sulfuric acid + potassium nitrate, washing + gibberellic acid, washing + potassium nitrate and stratification + potassium nitrate led to the highest seed vigor. The results of the second experiment revealed that the best treatments in terms of emergence percentage (EP) in the greenhouse were sulfuric acid + potassium nitrate (92%) and sulfuric acid + gibberellic acid (89%). Also, the minimum mean emergence time (MET) was obtained in washing + gibberellic acid (10 days). The highest seed vigor was found in washing + potassium nitrate and sulfuric acid + gibberellic acid. Totally, washing + gibberellic acid, washing + potassium nitrate, sulfuric acid + gibberellic acid and sulfuric acid + potassium nitrate were the best treatments to break Chinese lantern seed dormancy regarding germination percentage, MET and seed vigor.